Postać Jana Jakuba Rousseau i jego wpływ na współczesnych - Ludwisiak, Małgorzata (Acta Universitatis Lodziensis. Folia Historica, 2007)
This article is a part of a text in which the author tries to grasp a relation between sentimentalism and a huge interest for antiquity in a last three decades of the XVIIIth century. Following this relationship leads to Jean Jacques Rousseau (1712-1778). As well his work and its influence as the eighteenth century “antiquity mania” form a part of a new, secularized world in times of “critical years” (an expression of Paul Hazard). The author of the text tries to explain a phenomenon of an enormous influence of Rousseau on his contemporaries and an extreme editorial success of his works. The man - it’s proved - mentaly ill was able to attract the whole reading Europe. Rousseau questioned the base of Enlightenment: in times of adoration for civilization and reason he defended the rights of nature and feeling. He had paradoxical, firm opinions, enthusiasm and a good style. Still during his lifetime he became an object of worship not only thanks to his literary works (The New Heloise, Emile, or Education and Confessions) but also his controversial way of life. Since publishing his first discource he was trying to adjust himself to the radical opinions he anounced, so he broke with a social life of Paris, left the city and even started to dress differently. Rousseau was a very emotional person with an intense imagination. His emotions always predominated over his rational thinking and his work is full of discrepancies. During his life, especially in last twenty years, his mental and physical illness and paranoia manifested and intensified. There were many diagnosis made since the XlXth centaury but more important than that seems the writer himself used his illness. He didn’t even suspect a pathological character of his behaviour but in the same time it was a great excuse for him to avoid company of others and lead his solitary life, complying this way unconsciuosly with expectations of his readers. His admirors perceived him as a sufering man, a laic saint. In Poland Rousseau was the same popular as in the rest of Europe which can be proved by an example of three polish artistocrats: Helena Radziwiłłowa, Izabela Lubomirska and Izabela Czartoryska - their libraries, letters, gardens and collections of true and false remembrances of Jean Jacques. The free women collected antic pieces, read roman literature and constructed in their gardens false ruins with inscriptions from antic poets. The mutual deep relationship between these two important currents in the culture of late Enlightenment should be a subject of a separate study.